A Comprehensive Review of Diatom‐Bacterial Interactions Inferred From Bibliometric Analysis - Caiqin Hu; Zhen Shi; Tiehuan Hu; Yuan Gao; Qianfu Liu; Chao Wang (Reviews in Aquaculture, 2025)
Diatoms and bacteria have coexisted and coevolved for more than 200 million years, and their interactions have driven the processes of underlying major biogeochemical cycles. These complex and heterogeneous interactions span the range from synergistic to competitive and antagonistic, and they are regulated by diverse metabolites and biochemical mediators. Despite the significance of diatom–bacterial interactions in shaping aquatic food webs, driving nutrient cycles, and controlling algal blooms, the field currently lacks a comprehensive review of the current literature, research contents, and future research trends and perspectives. This review presents a comprehensive analysis of diatom–bacterial interactions by summarizing the information from current publications, including temporal trends, the most productive authors, journals, and countries, and illustrating current research contents, including regions, methods, foci, the interaction mechanisms and the environmental regulation. In addition, we discuss future research trends and perspectives. Our results indicate that most of the current research has been conducted in the ocean, using the methods of co‐culture experiments or field investigation combined with high‐throughput sequencing. The current research foci include the mechanisms of multiple cell‐to‐cell synergistic, competitive, antagonistic interactions, and multiple interactions regulated by biochemical molecules, and potential biotechnological applications. Furthermore, the future trends in this research field concern the underlying mechanisms of variation in diatom–bacterial interactions influenced by environmental changes and the possible applications. This review provides a comprehensive perspective on diatom‐bacterial relationships as well as a guide to future research.